فعالية طريقة التسوق عبر النوافذ بمساعدة بطاقة القصة لتحسين إتقان المفردات لطلبة الصف الحادي عشر - Bakri, Mubassyirah; Farkan, Kesin Betri Farkan (Al Ibrah: Journal of Arabic Language Education, 2020)
This research discusses how the effectiveness of the window shooping method assisted by story cards to improve the vocabulary mastery of grade XI students at MAN Palopo. This study aims to (1) find out how Arabic language learning uses  the window shooping method assisted by story cards to improve the mastery of vocabulary of grade XI students at MAN Palopo (2) to find out the effectiveness of  the window shooping method assisted by story cards to improve the mastery of vocabulary grade XI students at MAN Palopo. This type of research is classroom action research, the data collection method is action observation, field notes, and test sheets. The results of this study are (1) classroom action research conducted by the researcher can be concluded that the window shooping method is effective to be applied to grade XI students (Research Class) by seeing an increase in the results of students' Arabic vocabulary mastery which increases through the application of the window shooping method assisted by story cards. (2) The percentage increase in the first cycle can be seen that out of 24 students, 18 students completed the program with a percentage (75%), while 6 students completed the program with a percentage (25%). As for the second cycle, it can be seen that out of 24 students, 22 students completed with a percentage (91.7%), while those who have not completed as many as 2 students with a percentage (8.3%). From cycle I to cycle II, there was an increase in learning outcomes by (16.7%). Thus, in cycle II, the learning results are said to be complete. تناقش هذه الرسالة كيفية فعالية طريقة التسوق عبر النوافذ بمساعدة بطاقة القصة لتحسين إتقان المفردات لطلبة الصف الحادي عشر في المدرسة العالية الحكومية فالوفو. تهدف هذه الدراسة إلى (1) معرفة تعليم اللغة العربية بطريقة التسوق عبر النوافذ بمساعدة بطاقة القصة لتحسين إتقان المفردات لطلبة الصف الحادي عشر في المدرسة العالية الحكومية فالوفو. (2) فعالية طريقة التسوق عبر النوافذ بمساعدة بطاقة القصة في زيادة إتقان المفردات لطلبة الصف الحادي عشر في المدرسة العالية الحكومية فالوفو. هذا النوع من البحث هو البحث الإجرائي الصفي، وأساليب جمع البيانات هي ورقة الملاحظة، الإختبار، ملاحظة الميدانية، والتوثيق. نتائج هذا البحث هو: (1) بحث الإجرائي الصفي أجرته الباحثة يمكن استنتاج أن طريقة تسوق عبر النوافذ فعالة للتطبيق على طلبة الصف الحادي عشر (فصل البحث) من خلال النظر في الزيادة في نتائج إتقان الطلبة للمفردات العربية والتي تزداد من خلال تطبيق طريقة تسوق عبر النوافذ بمساعدة بطاقة القصة. (2) يمكن ملاحظة نسبة الزيادة في الدورة الأولى أنه من بين 24 طلبة ، أكمل 18 طلبة بنسبة مئوية (75٪)، بينما أولئك الذين لم يكملوا ما يصل إلى 6 طلبة بنسبة مئوية (25٪). أما بالنسبة للدورة الثانية فيمكن ملاحظة أنه من بين 24 طلبة، أكمل 22 طلبة بنسبة مئوية (91.7٪)، بينما كان أولئك الذين لم يتم إكمالهم طالبين بنسبة مئوية (8.3٪). من الدورة الأولى إلى الدورة الثانية كانت هناك زيادة في نتائج التعلم بنسبة (16.7٪). وهكذا في الدورة الثانية يقال إن نتائج التعلم كاملة.